PERKEMBANGAN SPODOPTERA LITURA F. (LEPIDOPTERA: NOCTUIDAE) PADA KEDELAI - Hendrival Hendrival; Latifah Latifah; Rega Hayu (Jurnal Floratek, 2013)
ABSTRACT A research on behavior of pest S. litura on two varieties of soybean has been done in Blang Manyak Village, Sawang Sub district, North Aceh District from January–May 2013. The research was arranged in a field experiment with two treatments of soybean varieties, that is Kipas Merah and Anjasmoro.  Each treatment was repeated 20 times to obtain 40 units of the experiment. Variables measured included damage intensity of S. litura, trichome density of leaves, yield components, and resistance evaluation. The relationships between yield components and damage intensity of S. litura were analyzed with regression and correlation. The results showed that damage intensity of S. litura on Kipas Merah was lower than that on Anjasmoro. Loss of soybean yield components on both varieties was influenced by the damage intensity of S. litura. There was a negative correlation between damage intensity of S. litura and soybean yield components on both varieties.  Kipas Merah was moderately resistant and Anjasmoro was susceptible against S. litura.  Resistance differences of both varieties were influenced by trichomes density of the leaves.